STUDI DESKRIPTIF PELUANG DAN TANTANGAN UMKM INDONESIA PADA MASA PANDEMI COVID-19 - Irwan Santoso (Jurnal Pendidikan Ekonomi Indonesia, 2021)
This writing is based on the background of the Covid-19 pandemic that has hit the world. One of the impacts is on the UMKM sector in Indonesia. Many small communities were affected by the pandemic, based on data received by the Ministry of Cooperatives and Small and Medium Enterprises, there were at least 300,000 umkm affected by Covid-19 as of August 11, 2020. This article was written to see the opportunities and challenges of UMKM in Indonesia during the Covid-19 pandemic. This writing conducts a search for information and information needed from various media that are literature, this media as a support and support for writing. These media include: books, journals, proceedings, articles and online news. In addition to using literature taken also from observations in several UMKM in Bandung as a comparison of data. The results of the discussion show that there are opportunities that are used by umkm actors such as: Taking advantage of e-commerce platforms, digital marketing, using the CRM concept and participating in the government's economic recovery (PEN) program. In addition to opportunities that can be exploited by UMKM players, there are challenges that UMKM players need to anticipate during the Covid-19 pandemic, such as: difficult supply of raw materials, decreased sales and falling demand.